ANALISIS SEGMENTING, TARGETING, POSITIONING PERUSAHAAN DAERAH PASAR SURYA UNTUK MENINGKATKAN EKSISTENSI PASAR TRADISIONAL SURABAYA - Pramana, Bambang; Nabilah Aini, Saqofa (Investama : Jurnal Ekonomi dan Bisnis, 2024)
This research aims to determine segmenting, targeting and positioning of PD Pasar Surya's efforts to maintain and increase the existence of traditional markets in Surabaya. The main focus in this research is how segmenting, targeting, and positioning are the efforts of the Surya Market Regional Company in mapping markets, market targets, and can create the minds of buyers and traders in managing traditional markets, with the hope of increasing the existence of traditional markets in the current era of modernization. This research uses a qualitative approach, by conducting interviews, observations, and documents supporting the literature on the development of Traditional Markets in Surabaya. The results of this research show that the Surya Market Regional Company has made efforts to manage traditional markets to increase market existence. Through segmenting, targeting, positioning analysis, it focuses on structuring, management, regulation and revitalization to be able to compete with the modern market. Geographic segmentation is carried out through strategic market placement tailored to the type of sales, demographics of all ages, while psychographics are adjusted to the needs of traders or buyers. Targeting is adjusted to the type of sales and market space placement. Positioning is based on price and quality, market visitors and competitors.